Dissecting the phenotype of supernumerary marker chromosome 20 in a patient with syndromic pierre robin sequence: Combinatorial effect of gene dosage and uniparental disomy. (2nd April 2015) - Izumi, Kosuke; Kubota, Noriko; Arakawa, Michiko; Takayama, Masayoshi; Harada, Yukiko; Nakamura, Tomohiko; Nishi, Eriko; Hidaka, Eiko
Abstract : Clinical phenotypes in individuals with a supernumerary marker chromosome (SMC) are mainly caused by gene dosage effects due to the genes located on the SMC. An additional effect may result from uniparental disomy (UPD). Consequently, the occurrence of UPD may be a confounding factor in identifying genotype‐phenotype correlations in SMC syndromes. Here, we report on a patient that illustrates this problem; the phenotype of this patient was a consequence of a combined effect of gene dosage and UPD. The proband showed facial dysmorphisms, growth retardation and developmental delay. G‐band karyotype of the proband's peripheral blood showed the presence of mosaic SMC. A SNP array analysis documented maternal UPD20 and 20p duplication. It is known that maternal UPD20 causes prenatal onset growth retardation and feeding difficulties. By contrast, duplication of 20p causes facial dysmorphisms, micrognathia, cleft palate, developmental delay and vertebral anomalies. Our classification of the proband's phenotype showed a mixture of these two effects. Therefore, we suggest the routine use of genome‐wide SNP array towards the detailed genotype‐phenotype correlations for SMC syndromes. © 2015 Wiley Periodicals, Inc.